2023
DOI: 10.1101/2023.05.18.23290199
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Role of Oestrogen in Female Skeletal Muscle Ageing: A Systematic Review

Abstract: Ageing is associated with a loss of skeletal muscle mass and function that negatively impacts the independence and quality of life of older individuals. Females demonstrate a distinct pattern of muscle ageing compared to males, potentially due to menopause where endogenous sex hormone production declines. This systematic review aims to investigate the current knowledge about the role of oestrogen in female skeletal muscle ageing. A systematic search of MEDLINE complete, Global Health, Embase, PubMed, SPORTDisc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…(22) Recent research results demonstrate that decreasing estrogen levels have the potential to affect skeletal muscle strength in the elderly. (23) Administration of the estrogen group (17ß-estradiol) has the effect of preventing the decrease in skeletal muscle activity. (24) With regard to aging, it has been shown that postmenopausal women experience a rapid decline in muscle mass and strength.…”
Section: Sex Steroid Hormone and Handgrip Strengthmentioning
confidence: 99%
See 1 more Smart Citation
“…(22) Recent research results demonstrate that decreasing estrogen levels have the potential to affect skeletal muscle strength in the elderly. (23) Administration of the estrogen group (17ß-estradiol) has the effect of preventing the decrease in skeletal muscle activity. (24) With regard to aging, it has been shown that postmenopausal women experience a rapid decline in muscle mass and strength.…”
Section: Sex Steroid Hormone and Handgrip Strengthmentioning
confidence: 99%
“…(26,27) In addition, the estrogen replacement therapy program is also beneficial in maintaining skeletal (15)(16)(17) muscles during aging. (23) In addition, it has been shown that in postmenopausal women, female sex hormones play an important role in skeletal muscle mass. Therefore, female sex hormone therapy is considered in elderly women for the maintenance of skeletal muscle mass.…”
Section: Sex Steroid Hormone and Handgrip Strengthmentioning
confidence: 99%